KAJIAN EFEK KETIDAKSTABILAN ELEKTROHIDRODINAMIK PADA SAMPEL HOMEOTROPIK KRISTAL CAIR NEMATIK - , RISTI SURYANTARI, Dr. Yusril Yusuf ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Electrohydrodinamic (EHD) effects of nematic liquid crystal MBBA (4â- methoxy-benzylidene-4-butyl-aniline) homeotropic sample with different thickness 50 Î¼m and 100 Î¼m have been observed. EHD could be observed by polarizing microscope connected to CCD camera. Liquid crystal gave an active respond in the applied electric field. Various convection patterns were considered. Stripe periodic pattern called Williams Domain (WD) with stripe direction perpendicular to the initial unperturbed orientation of director n was appeared at VWD. An unstable pattern called Fluctuating Williams Domain (FWD) appeared at VFWD>VWD. Another typical pattern which was more stationer than FWD was formed at VGP>VFWD. Critical voltage, VWD, VFWD and VGP, for sample 1 and sample 2, had the same values. The thickness did not affect critical voltage. It affected the stripe line width in patterns. Phase diagram was showed in frequency-voltage plane. Increasing frequency caused increasing critical voltage but the relation was not linear